2011
DOI: 10.5137/1019-5149.jtn.5151-11.3
|View full text |Cite
|
Sign up to set email alerts
|

Transforaminal epidural steroid injection via a preganglionic approach for the treatment of lumbar radicular pain

Abstract: AIm:To evaluate the effectiveness of transforaminal epidural steroid injection (TFESI) for lumbar radiculopathy with respect to effect of injection levels, gender, and age group. mAterIAl and methOds: Hundred-fifty-three consecutive patients who underwent to lumbar TFESI were enrolled. The outcomes were measured by using a visual numeric scale (VNS), NASS and EQ-5D. The relationship between possible outcome predictors and the therapeutic effect were evaluated.results: All the patients completed the 2nd year fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Two included long-term follow-up for 1 year or more. 16,28 However, the studies with long-term followup had mixed results, in that one was positive and the other negative at long-term follow-up. The remainder analyzed periods up to 6 months, and all demonstrated that a single epidural injection was effective in alleviating LBP from spinal stenosis and lumbar radiculopathy.…”
Section: Single Injectionmentioning
confidence: 96%
See 3 more Smart Citations
“…Two included long-term follow-up for 1 year or more. 16,28 However, the studies with long-term followup had mixed results, in that one was positive and the other negative at long-term follow-up. The remainder analyzed periods up to 6 months, and all demonstrated that a single epidural injection was effective in alleviating LBP from spinal stenosis and lumbar radiculopathy.…”
Section: Single Injectionmentioning
confidence: 96%
“…10,11 Nine studies demonstrated that ESI was beneficial in the short term for treating radicular pain of any cause, and the single study that included a control group demonstrated that NSEI was equally effective. 28,[30][31][32][33][34][35][36][37] Four studies reported on radicular pain because of any cause other than spinal stenosis, and found that ESI was effective at reducing radicular symptoms in the short term. 29,[38][39][40] Two of these studies differentiated between low back and radicular pain, and ESI was equally effective at reducing both pain types.…”
Section: Radicular Pain From All Causesmentioning
confidence: 99%
See 2 more Smart Citations
“…A dose-dependent impairment in immune function stems from transcriptional changes that suppress inflammatory genes (via transrepression), upregulate anti-inflammatory genes (via transactivation) and inhibit B and T cells and phagocytes [57]. Although retrospective studies on infection following ESI are lacking, case reports indicate infection may follow ESI in patients with preexisting immunosuppressive conditions, which include diabetes, cancer (with or without metastasis), neutropenia, oral steroid use, prior history of infections [58] and renal failure [59]. Other conditions that also limit immune function include HIV infection, alcoholic cirrhosis and asplenia [60].…”
Section: • Immune Systemmentioning
confidence: 99%